A facile approach to fabricating graphene/waterborne epoxy coatings with dual functionalities of barrier and corrosion inhibitor. (10th June 2022) - Liu, Suyun; Wang, Xuewan; Yin, Qi; Xiang, Xiongzhi; Fu, Xian-Zhu; Wang, Xian-Zong; Luo, Jing-Li
Highlights: A facile approach to fabricating C-G/WEP and S-G/WEP composite coatings with dual functionalities as barriers and corrosion inhibitors was developed. The impedance of the C-G/WEP and S-G/WEP coatings is enhanced by more than two orders of magnitude compared with that of WEP coatings. The presence of surfactants facilitates the dispersion of C-G and S-G nanosheets in both the solution and the composite coatings. The surfactants endow inhibition ability of the coatings, thereby the composite coatings effectively protect the underlying Q235 steel against corrosion. This work exemplifies a facile yet environmentally-friendly approach to preparing graphene composite coatings and may enable the large-scale production of graphene anticorrosion coatings. Abstract: A facile and environmentally-friendly method is developed to prepare graphene/waterborne epoxy (WEP) composite coatings. The graphene nanosheets are produced with electrochemical-exfoliation in the solution containing surfactants, cetyl trimethyl ammonium bromide (CTAB) and sodium dodecyl sulfate (SDS). The nanosheets containing solution thus formed are subjected to a quick dialysis and then directly used as a diluent for WEP without any further treatment. This preparation method overcomes the commonly identified problems of aggregations and 'corrosion promotion' effect associated with graphene, and increases the impedance of the composite coatings by more than two orders of magnitude. The analysis of anticorrosion performance suggested that the presence of surfactants not only improves the dispersibility of graphene nanosheets but also endows the composite coatings with both barrier and corrosion inhibition capabilities. The strategy reported herein may pave the path to the large-scale production of graphene anticorrosion coatings.